Stress among Parents of Children with Mental Retardation (Bangladesh Journal of Medical Science, 2013)
Mental retardation is one of the most prevalent developmental disabilities of the children globally. Family is the main source of support for those disable children in any society. Parents experience enormous physical and mental stress to tackle the mentally retarded children. This present comparative cross-sectional study tried to compare difference of mental and physical stress between the parents of children with mental retardation and the parents of children with no mental retardation. It included 220 parents, 110 of whom had children with mental retardation and another 110 parents of children with no mental retardation. To assess stress, A Quick Stress Assessment Test (QSAT) (Vaz, 1995) was used, which comprised two parts: physical and mental, former with 19 items and latter with 21 items. Data were collected with a self-administered questionnaire and analyzed by using SPSS software. To check differences of stress scores and gender differences of stress,t test and ?2 tests were applied as required. The study revealed that the parents of children with mental retardation (PCMR) shared significantly greater stress score (34.27) than the parents of children with no mental retardation (PCNR) (21.66), [t(218)= 2.63, p=0.001]. Mental stress score was significantly higher among PCMR (33.57) than the PCNR (26.46) [t(218)= 3.87; p=0.002] while physical stress score was insignificantly higher among PCMR (20.43) than the PCNR (18.66). Majority of the parents with mentally retarded children (71.4% mothers and 67.5% fathers) had higher mental stress than physical stress [?2 (1)=22 43, p=0.024]. Mothers had significantly higher mental stress score than the fathers of mentally retarded children [t(109), p=0.025]. Special measures like early diagnosis, prompt treatment and counseling for mental and physical stress of the parents along with provision of need based rehabilitation services for the mentally retarded children at different levels to reduce the stress burden of their parents. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13354 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.74-80